Spinal Tuberculosis with Paraplegia in Pregnancy: a Case Report with Management of Spinal TB in Pregnancy - Sushruti Kaushal; Santosh Kumar Dora; Sunil Thakur (Journal of Nepal Medical Association, 2015)
Spinal tuberculosis leading to paraplegia is uncommon in pregnancy and is a diagnostic and therapeutic challenge. We report a case of tubercular paraplegia presenting at 35 weeks of gestation. She was managed with Anti-tubercular drugs and did not require surgical intervention. Her neurological status improved and she was allowed to go in labour. She delivered a healthy term infant by cesarean. At three months follow-up, both mother and child are doing well.